The Role of Facilitators in Blended Foreign Language Teaching - Zhussupova, R. F.; Shelestova, T.Yu.; Kalizhanova, A.N. (L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY, 2023)
This training manual is designed for bachelor students, master students, and Ph.D. students of the educational program «Foreign language: two foreign languages», and «Translation studies» and for everyone who assists groups to learn, whether formally or informally, through workshops, courses or Massive open online courses (MOOC), as facilitator or teacher or trainer. The purpose of the training manual «The role of facilitators in blended foreign language teaching» is to create communicative competence among trainees, including professional-specialized competence to provide a skilled facilitator approach. This training manual relies on descriptions of how to use MOOC, and Web 2.0 tools in the training process, to show the strategies for successful facilitation and how to become a skillful facilitator. Descriptions include more details and reveal more nuances and layers of the role of facilitators in blended foreign language teaching and facilitated sessions’ scenario for the massive open online course. Today, MOOCs combine several advantages over the traditional education system: high-quality content from the world's best universities, flexible schedules, and this training manual has ascertained practical instructional strategies that are effective in planning, implementing, and facilitating MOOC in blended foreign language teaching. This research is funded by the Science Committee of the Ministry of Science and Higher Education of the Republic of Kazakhstan on the topic «Facilitators in Advanced Training of Teachers in Blended Learning: Efficiency Assessment, Methodology, Vectors of Competence Development» (2021–2023) (IRN AR09260118).